The role of personality congruence, perceived quality and prestige on ready-to-wear brand loyalty - ERDOĞMUŞ, ZEYNEP İREM (My University, 2012)
Purpose: In today's marketplace, successful branding requires building strong bonds with the consumers, by creating favorable, strong and unique brand associations in consumer minds. This study aims to identify the role of functional (perceived quality) and symbolic brand associations (personality congruence and brand prestige) in creating brand loyalty in the ready-to-wear sector from the perspective of Generation Y consumers. Design/methodology/approach: The research employs a structural equation modeling method based on data collected from 564 individuals born between 1977 and 1994. Turkey is chosen as the context of the study based on the fact that the ready-to-wear sector is one of the leading sectors in the country and about 30 percent of the population are Generation Y consumers. Findings: The findings of the study reveal that perceived quality has a direct positive effect on brand loyalty, suggesting appearance and product quality perception are critical in the preferences of Generation Y consumers. Personality congruence and brand prestige, on the other hand, have an indirect positive effect on brand loyalty with the mediation of appearance and product quality. Practical implications: The practitioners in the sector should devote special attention to appearance quality together with product quality, and construct a high quality and prestigious brand image with the personality traits of sincerity, competence, and excitement. Originality/value: This study has contributions to branding, ready-to-wear, and Generation Y literature combining several important dimensions into a structural model, and examines the interrelationships among these dimensions as well as their effect on brand loyalty. © Emerald Group Publishing Limited.
Keywords: Brand loyalty; Brand management; Brand personality; Generation Y; Perceived quality; Prestige; Ready-to-wear branding; Turkey